Hukuman dan Tanggung Jawab - Petrus CKL Bello (Pusat Kajian Lembaga Pemasyarakatan, Fakultas Hukum, Universitas Kristen Indonesia, 2025)
In his book Punishment and Responsibility, H.L.A. Hart presents moral arguments related to punishment and responsibility or related to the problem of punishment and guilt. However, what Hart offers is not the morality of guilt and punishment in general, but the official morality of guilt and punishment-morality for public officials. As a result, moral doctrines that have been officially institutionalized in public institutions and legal rules are separated from similar or analogous doctrines related to parts of moral life that are not institutionalized, for example in the morality of personal relationships. According to Hart, public interest in the topic of punishment and guilt is quite large even though society is still plagued by confusion caused by uncertainty and doubt about the morality of punishment conveyed by competing theories of punishment. Punishment according to Hart is not part of ideal justice, punishment is only a mechanical and dangerous means of protection that requires the greatest wisdom and humanity to turn it into a means of reform. For such a view, the moral justification for punishment and guilt lies in its impact in contributing to crime prevention and the social adjustment of criminals. According to Hart, punishment must be given to violations that are committed voluntarily.